TRANSLADDER: INTEGRATING GAME-BASED LEARNING INTO TRANSLATION CLASS - Saleh, Ainul Adiba; Ahmad, Haryati; Shahidan, Sharifahtun Naim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
In today’s increasingly globalized world, translation studies play a significant role in training future translators to translate written documents. Their translation work would be one of the means to bridge the gaps in the knowledge, skills, and cultures among peoples of different nations and countries. However, most students of translation courses experience difficulties in understanding translation theories and procedures, and in applying them when translating materials for their coursework. The Transladder: Translation Board Game (henceforth referred to as Transladder) is an interactive educational tool developed to assist and motivate students in translation classrooms. Adapted from the Political Fun Race board game by Abdul Rahim et al. (2018), which was designed for students taking a political science course, Transladder aims to engage students in foundational translation theory and procedures through a game-based learning approach. Its primary objectives are to equip learners with the ability to explain general terms and concepts in translation studies, and to identify the translation procedures introduced by Vinay and Darbelnet, two prominent scholars in translation studies. A questionnaire was developed and distributed as an online survey through Microsoft Forms to students taking the BBM321: Introduction to Principles of Translation course for academic session I 2025/2026 (October 2025 - February 2026) at Universiti Teknologi MARA (UiTM) Johor Branch, Segamat campus. This was to gain the students’ perception of Transladder as an instructional tool for the course. The findings revealed that the majority of the respondents reported high levels of enjoyment, engagement, and perceived learning value from the game. Their recommendations of the game to peers taking similar translation courses demonstrated a positive learning experience and engagement with the game.